Synthesis of 2-(α-Naphthyl)-Halogenochromones and Study of their Toxicity to Fish - Kuberkar, S.V.; Vibhute, Y.B. (Asian Journal of Chemistry, 2010)
2-(α-Naphthyl)-halogenochromones were prepared by condensing 1-naphthaldehyde and 2-methoxy-1-naphthaldehyde with 3-and/or 5-halogeno substituted hydroxy acetophenone. The intermediate chalcones were obtained. These chalcones were treated with selenium dioxide in isoamyl alcohol and as a result of oxidative cyclization, 2-(α-naphthyl)-halogenochromones were isolated. The structures have been confirmed on the basis of elemental analysis and IR spectral data. All these altogether new chromones were tested for their toxicity to fish.